2020
DOI: 10.1186/s13054-020-02876-9
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound findings in patients with COVID-19 pneumonia

Abstract: Since December 2019, the outbreak of pneumonia caused by a new coronavirus [1], which was later identified as coronavirus disease 2019 (COVID19), has infected more than 410,000 patients globally according to the situation report of World Health Organization. Lung ultrasound is an important tool for the diagnosis and follow-up of pneumonia in neonates, children, and adults [2][3][4]. Recent CT reports demonstrated that most of the lesions were distributed peripherally in the lung, which facilitates detection by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
143
4
11

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(180 citation statements)
references
References 6 publications
17
143
4
11
Order By: Relevance
“…Nevertheless, it should be considered that the speci city and the positive predictive of the same LUS signs may be lowered in a normal setting of non epidemic COVID-19. Indeed, the sonographic ndings described in our case series and in the current available literature on this topic 11,12,13,14,15 shows a considerable overlap with many other lung diseases. An irregular pleural line with increased B-lines may be visible in ARDS, heart failure, nephrotic syndrome, bacterial pneumonia, other viral pneumonia, also minimal pleural effusion, hydropneumothorax, brosis, pulmonary contusion, exacerbations of chronic obstructive pulmonary diseases and neoplastic lymphangitis 16 .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Nevertheless, it should be considered that the speci city and the positive predictive of the same LUS signs may be lowered in a normal setting of non epidemic COVID-19. Indeed, the sonographic ndings described in our case series and in the current available literature on this topic 11,12,13,14,15 shows a considerable overlap with many other lung diseases. An irregular pleural line with increased B-lines may be visible in ARDS, heart failure, nephrotic syndrome, bacterial pneumonia, other viral pneumonia, also minimal pleural effusion, hydropneumothorax, brosis, pulmonary contusion, exacerbations of chronic obstructive pulmonary diseases and neoplastic lymphangitis 16 .…”
Section: Discussionsupporting
confidence: 51%
“…Frequently reported LUS ndings are the appearance of multiple, con uent or not, B-lines, a thickened and irregular pleural line and small super cial or large areas of consolidation 11,12,13 . Also minimal or rarely larger pleural space uid effusions has been evidenced 14,15 .…”
Section: Introductionmentioning
confidence: 98%
“…concluded that ‘a rapid teaching program is sufficient to provide gynecologists and obstetricians who are already skilled in obstetric and/or gynecological ultrasound examination with the theoretical skills necessary to recognize specific lung ultrasound patterns.’, adding that they believe that their course ‘represents one possible model for implementing lung ultrasound education and might be a useful launch‐pad for gynecologists and obstetricians involved in the management of pregnant patients with confirmed or suspected COVID‐19.’ We agree that a short training course is important to improve the knowledge and skill of practitioners. The usefulness of lung ultrasonography in the diagnosis of lung pathology in pregnant women with COVID‐19 has been confirmed 2 . Yet, the limited availability of data on lung ultrasound findings in COVID‐19 is a challenge, particularly as various non‐specific forms of lung abnormality are observable in this disease 2 .…”
mentioning
confidence: 99%
“…• B artifact -B line or lighthouse sign, often multiple, grouped, leading to the waterfall sign; • loss of A line; • pleural roughening / cobblestone; • reduction of pleural sliding; • discontinuous pleural line; • subpleural consolidation -multifocal small nontranslobar or translobar, with or without mobile air bronchogram; • posterior, basal and right-sided most frequent location; • without pleural effusion or very rare incidence of it [1,2]. It is noteworthy that these changes are not specific for COVID19 infection as they also occur in venous pulmonary hypertension / cardiogenic interstitial or alveolar edema or interstitial fibrosis.…”
mentioning
confidence: 99%
“…• A lines or insignificant B lines = 0 points (normal); • significant B lines (respectively more than 3 per intercostal space) = 1 point; • coalescent B lines with or without small subpleural consolidations = 2 points; • obvious, macroscopic, segmental or more extensive lung consolidation = 3 points. The proposed score has both the ability to express severity and to monitor the evolution and to guide the treatment with ventilation and posture [1]).…”
mentioning
confidence: 99%